Spacecraft TT&C and Information Transmission Theory and Technologies - Liu, Jiaxing; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
Spacecraft TT&C and Information Transmission Theory and Technologies introduces the basic theory of spacecraft TT&C (telemetry, track and command) and information transmission. Combining TT&C and information transmission, the book presents several technologies for continuous wave radar including measurements for range, range rate and angle, analog and digital information transmissions, telecommand, telemetry, remote sensing and spread spectrum TT&C. For special problems occurred in the channels for TT&C and information transmission, the book represents radio propagation features and its impact on orbit measurement accuracy, and the effects caused by rain attenuation, atmospheric attenuation and multi-path effect, and polarization composition technology. This book can benefit researchers and engineers in the field of spacecraft TT&C and communication systems. Liu Jiaxing is a professor at The 10th Institute of China Electronics Technology Group Corporation.
Introduction -- Theories and Technologies of Tracking & Orbit-Measuring -- Information Transmission Technologies -- Spread Spectrum TT&C -- Special issues on Radio Transmission Channel in C&T.
Keywords: Engineering; Physical measurements; Measurement; Aerospace engineering; Astronautics; Electrical engineering; Engineering; Aerospace Technology and Astronautics; Communications Engineering, Networks; Measurement Science and Instrumentation; Electronic books